1966
DOI: 10.1002/rds196612170
|View full text |Cite
|
Sign up to set email alerts
|

Some Rocket Results on Sporadic E

Abstract: In 1964 several rockets were fired in Hammaguir, Algeria, in order to study the sporadic E region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Two other papers reported on T e inside E s . Aubry et al (1966) showed two E s events. One case is that T e inside E s was 1/2 that of the ambient.…”
Section: Introductionmentioning
confidence: 96%
“…Two other papers reported on T e inside E s . Aubry et al (1966) showed two E s events. One case is that T e inside E s was 1/2 that of the ambient.…”
Section: Introductionmentioning
confidence: 96%
“…To take ac count of the possibility of an error due to aerodynamic heating as suggested by The ac probe results [Aubry et al (1966)] were obtained during the afternoon at…”
Section: Ionospheric Temperatures Below 140 Knmentioning
confidence: 99%
“…The Whitehead-Storey theory of sporadic E formation through the wind-shear mechanism has been developed in considerable detail [e.g., see Whitehead, 1967; Ax•ord, l!J67] and found to account for much of the observed data [Wright et al, 1967;Aubry et al, 1966;MacLeod, 1966;Young et al, 1967]. However, it is commonly found that low-altitude (85-95 km) sporadic E layers occur at positions that do not have any clear relationship to simultaneously observed neutral wind profiles [Wright et al, 1967;Aubry et al, 1966;Mac-Leod, 1966], and indeed the layers often appear to be located in regions of ionization divergence, in direct contradiction to the usual predictions of the wind-shear theory.…”
Section: Introductionmentioning
confidence: 99%